Long-term outcomes of different ablation strategies for ventricular tachycardia in patients with structural heart disease: systematic review and meta-analysis. Issue 1 (26th May 2017) - Briceño, David F; Romero, Jorge; Villablanca, Pedro A; Londoño, Alejandra; Diaz, Juan C; Maraj, Ilir; Batul, Syeda Atiqa; Madan, Nidhi; Patel, Jignesh; Jagannath, Anand; Mohanty, Sanghamitra; Mohanty, Prasant; et al.
Abstract: Aims: To compare the long-term outcomes of standard ablation of stable ventricular tachycardia (VT) vs. substrate modification, and of complete vs. incomplete substrate modification in patients with structural heart disease (SHD) presenting with VT. Methods and results: An electronic search was performed using major databases. The main outcomes were a composite of long-term ventricular arrhythmia (VA) recurrence and all-cause mortality of standard ablation of stable VT vs. substrate modification, and long-term VA recurrence in complete vs. incomplete substrate modification. Six studies were included for the comparison of standard ablation of stable VT vs. substrate modification, with a total of 396 patients (mean age 63 ± 10 years, 87% males), and seven studies were included to assess the impact of extensive substrate modification, with a total of 391 patients (mean age 64 ± years, 90% males). More than 70% of all the patients included had ischaemic cardiomyopathy. Substrate modification was associated with decreased composite VA recurrence/all-cause mortality compared to standard ablation of stable VTs [risk ratio (RR) 0.57, 95% confidence interval (CI) 0.40–0.81]. Complete substrate modification was associated with decreased VA recurrence as compared to incomplete substrate modification (RR 0.39, 95% CI 0.27–0.58). Conclusion: In patients with SHD who had VT related mainly to ischaemic substrates, there was a significantly lower risk of the composite primary outcome of long-term VA recurrence and all-cause mortality among those undergoing substrate modification compared to standard ablation. Long-term success is improved when performing complete substrate modification.